Answer:
For the independent value of 2, the equations generate the same dependent value ⇒ A
Explanation:
In the linear equation y = m x + b
- x is the independent variable
- y is the dependent variable
∵ y1 = 6x - 16
∵ y2 = 3x - 10
∵ x is the independent value
∵ y is the dependent value
∵ The two equations have same dependent value
→ Same dependent value means equate y1 and y2
∴ y1 = y2
→ Equate their right sides
∴ 6x - 16 = 3x - 10
→ Subtract 3x from both sides
∵ 6x - 3x - 16 = 3x - 3x - 10
∴ 3x - 16 = -10
→ Add 16 to both sides
∵ 3x - 16 + 16 = -10 + 16
∴ 3x = 6
→ Divide both sides by 3
∴ x = 2
∴ For the independent value of 2 the equations generate the same
dependent value